Acute fulminant drug induced necrotizing pancreatitis in a patient with ankylosing spondylitis - Pablo Miramontes; Carlos Montilla; Ismael Calero-Paniagua; Andrés Plata (Sociedade Galega de Medicina Interna, 2015)
Drug-induced acute necrotizing pancreatitis is a rare adverse event, although it has been reported in association with different drugs, including non-steroidal anti-inflammatory drugs, disease-modifying antirheumatic drugs, and analgesic agents commonly used in rheumatology. In different reviews of the pancreotoxicity of drugs, infliximab and etanercept are mentioned among all medications implicated in drug-induced pancreatitis, but clinical cases of acute pancreatitis complicating treatment with these anti-TNF-α agents have been exceptionally reported. We describe a patient with ankylosing spondylitis treated with etanercept, who developed an acute fulminant necrotizing pancreatitis that resulted in death. Doctors should pay close attention to patients taking biologic drugs in which a complaint of abdominal pain lasting for several days with no apparent cause may require a prompt referral for medical consultation.